WAKAF TUNAI MENURUT PANDANGAN FIQH SYĀFI‘IYAH DAN FATWA MAJELIS ULAMA INDONESIA NO.2 TAHUN 2002 TENTANG WAKAF UANG - Mustafa Kamal (Islam Futura, 2015)
This study discusses the cash waqf according to Syāfi‘iyah school and the Fatwaaccording to the Indonesian Ulema Council (MUI). The problem questions that wantto be answered through this research are related to the notion of waqf in the viewSyāfi‘iyah and MUI, cash waqf law in perspective and rationale Syāfi‘iyah againstfatwa MUI and the cash endowments, as well as the understandingof cash waqfarguments. From this study, it is found that the MUI fatwa stipulates that charitablemoney is permissible or legal, while Syāfi‘iyah assumed that it is illegitimate. MUIunderlying consideration in the opinion of Ḥanafī schools that allow endowmentsdirhams and dinars on the basis of istiḥsān bi al-'urf. Furthermore, according to theprinciple syafi'iyah waqf object is to be the principal eternal object or substance(baqā' 'aynih), which is not destroyed after use. Whereas money can be destroyedlike food.